The Stature of the Self-employed and its Premium - Cornelius A. Rietveld; Jolanda Hessels; Peter van der Zwan (Tinbergen Institute, 2014)
This discussion paper resulted in a publication in 'Economics and Human Biology' (forthcoming). Taller individuals typically have occupations with higher social status and higher earnings than shorter individuals. Further, entrepreneurship is associated with high social status in numerous countries; hence, entrepreneurs might be taller than wage workers. Using data from the German Socio-Economic Panel (2002-2010), we find that a 1 cm increase in an individuals height raises the probability of being self-employed (the most common proxy for entrepreneurship) versus paid employed by 0.16 percentage-points. Within self-employment the probability of being an employer is increased by 0.11 percentage-points as a result of a 1 cm increase in height whereas this increase is 0.05 percentage-points for an own-account worker. Furthermore, we confirm that a height premium in earnings exists for not only paid employees, as indicated by prior studies, but also for self-employed individuals. An additional 1 cm in height is associated with a 0.44% increase in hourly earnings for paid employees, and a 0.87% increase for self-employed individuals. The predicted earnings differences between short and tall individuals are substantial. Short paid employeesfirst quartile of heightearn 15.5 Euros per hour whereas tall paid employeesthird quartile of heightearn 16.5 Euros per hour; in self-employment the earnings are 12.8 and 14.4 Euros per hour, respectively. Another novel finding is that we establish the existence of a height premium for work and life satisfaction, but only for paid employees. Finally, our analysis reveals that 44% of the height premium in earnings is explained by differences in educational attainment whereas the height premium in work and life satisfaction is only marginally explained by education.
Keywords: J24; J31; 330; Self-employment; Stature; Height premium; Education; Life satisfaction